Trade Globalization and Price Wars - Awok, Mbum Patrick; O, Nnabuko Justie; O, Odama Abraham (Asian Journal of Empirical Research, 2012)
This is a library survey of trade globalization and price wars which examine the deepening role trade globalization and the devastations price wars can degenerate. The study went through time, space and contributions of trade to globalization and enlisted a few examples of price wars and proffer solutions. Price wars were identified as plagues that do the nations, industries and individuals no good. Price wars were seen in the Chinese home appliances industry, Brazilian bananas industry, e-book sector, and airbus and Boeing airlines industry costing global superpowers players billions of United States dollars. The role and contributions of world trade organization (WTO) examined using its statistical data of simple ratios and percentages to analyze world economies.